A Readiness Assessment Tool for Smart City Implementation in Small and Rural Municipalities - Mashau, Nkhangweni Lawrence; Kroeze, Jan Hendrik (Journal of Information System and Informatics, 2024)
Small and rural municipalities are lagging in terms of implementing a smart city. These municipalities have limited resources to provide basic services to the citizens. There is a need for these municipalities to implement a smart city to manage resources effectively. However, an assessment tool to assess small and rural municipalities’ readiness for smart city implementation is lacking. This article offers such an assessment tool tailored specifically to assess small and rural municipalities’ readiness for smart city implementation. Design science research methodology (DSR) was used in a wider study to develop a related smart city readiness framework. In the preceding cycles of the DSR study, a literature review was used to provide relevant data for the construction of a conceptual framework, which was validated and improved using semi-structured interviews in a second and third cycle. The last cycle of the research developed and validated an assessment tool as an artefact that could be used to address critical issues, including limited resources and governance complexities that are unique to these municipalities. The findings showed that the proposed tool covered all the salient aspects, except for the aspect of smart buildings that are capable of collecting data without human intervention. This element was added to the final assessment tool. The tool can be used by personnel and consultants who are responsible for developing or implementing a smart city in small and rural municipalities. Furthermore, what makes this assessment tool unique is its alignment with the needs of small and rural municipalities. It was validated through participatory and expert reviews, providing a reliable instrument for policymakers and municipality managers in making an informed decision toward the readiness assessment of a smart city. A formula to calculate a municipality’s readiness level quantitively as a percentage, as well as a proposed evaluation heuristic, is also provided. The final, revised assessment tool prompts actionable insights informing the implementation of a smart city in small and rural municipalities.